Allothetic orientation and sequential ordering of places is impaired in early stages of Alzheimer's disease: corresponding results in real space tests and computer tests - KALOVA, Eva; VICEK, Kamil; JAROLIMOVA, Eva; BURES, Jan (Behavioural brain research, 2005)
Spatial disorientation and learning problems belong to the integral symptoms of Alzheimer's disease (AD). A circular arena for human subjects (2.9 m diameter, 3 m high) was equipped with a computerized tracking system, similar to that used in animals. We studied navigation in 11 subjects diagnosed with early stages of Alzheimer's disease (AD), 27 subjects with subjective problems with memory or concentration, and 10 controls. The task was to locate one or several unmarked goals using the arena geometry, starting position and/or cues on the arena wall. Navigation in a real version and a computer map view version of the tests yielded similar results. The AD group was severely impaired relative to controls in navigation to one hidden goal in eight rotated positions. The impairment was largest when only the cues on the wall could be used for orientation. Also, the AD group recalled worse than controls the order of six sequentially presented locations, though they recalled similarly to controls the positions of the locations. The group with subjective problems was not impaired in any of the tests. Our results document the spatial navigation and non-verbal episodic memory impairment in the AD. Similar results in real and map view computer tests support the use of computer tests in diagnosis of cognitive disturbances.